The evolution of the general criteria for the attribution of the legal capacity (Italian Review of Legal History, 2019)
The aim of this contribution is to make a brief exam, starting from the Roman legal system, of the criteria adopted to determine the achievement of puberty by the child, which involves the acquisition of the legal capacity in order to validly enter into legal agreements. The reflection, from a critical point of view, focuses on the analysis of the relationship between physical maturity, ascertained therefore with external criteria, and psychological, which is necessary to give the person that awareness that, to date, is regulated and indicated by art. 2 c.c. as "the ability to perform all acts".How is it established what is the right age for a minor to be considered an adult and therefore able to make legally binding choices?From the point of view of the typical approach of the Roman legal system, it is necessary to premise how, regarding a given problematic case, it is always solved, starting from a 'remedial' perspective rather than a defining one: consequently, also concerning the protection of minors, the sources that testify the situation in which the impuber found themselves are concentrated on the actions granted in defence of the latter, more than anything else.In the Roman legal system, therefore, there was no psychological parameter capable of disproving the passage from impubescence to puberty: it turned out to be a mere physical process whereby, when the full sexual maturity was reached, the full legal capacity was also considered automatically reached.The term impuber, therefore, identifies the person that, nowadays, we would call incapable; although the Romans did not leave us a true definition of 'legal capacity' and, therefore, on the contrary, of 'incapacity' in a modern sense, they conceptually distinguished between a legal capacity and a legal personhood. In fact, especially in the classical and postclassical era, legal agreements entered by persons who had not reached a certain age were automatically recognized as invalid, unless they were ratified by the legal guardian with the interposition of the appropriate auctoritas.A further element that must necessarily be taken into consideration in order to understand the evolutionary process concerning the protection of minors in the Roman system is the recognition of protection granted to persons under the age of twenty-five. After the age of puberty, the only obstacle to the child's ability to implement legally binding agreements was represented by inexperience.Having clarified what was the situation in ancient Rome, we can, in broad terms, see how in the Middle Age the term of the impubescent age and the criterion with which it was defined as such changed from the previous era, especially depending on the areas of reference.The passing, therefore, of the medieval age was a sort of connection between the result that the Romans had arrived at in terms of their legal capacity and what would later be provided for in the subsequent codifications. We see how in this period there is a 'maintain' of what was achieved by the Roman legal system without, however, further steps forward towards the criterion of attribution of the ability to act. There remains a formal criterion that guarantees, in essence, a decreasing protection as age grows.It seems to me then possible to notice how a fixed parameter taken as a basis for considering a young person capable of legally binding choices or not was in a certain sense arbitrary and how this methodology has remained unchanged over the centuries.A fact that now seems certain is that the concept of the legal capacity evolves as the legal thought goes on and is susceptible to interpretations and application methods that adapt it to the most diverse needs. The idea behind the concept of the legal capacity also concerns the parameter of relativity: it varies both according to the type of agreement to be performed and according to the age or legal situation of a given subject.The legal capacity, as mentioned above, relates to the possibility to enter into legally valid agreements, letting the legal system protect the choices made by an individual.Drawing on the brief considerations made so far, the question that arises most spontaneously concerns the assessment of the criterion used to give the full legal capacity: is the completion of a certain age really enough for a young person to be able to fully understand the acts that he implements? Would it not be fairer to ascertain the 'maturity' of the individual more substantially and not only formally?